The Increasing Effect of Neighborhood Racial Composition on Housing Values, 1980–2015. (4th September 2020) - Howell, Junia; Korver-Glenn, Elizabeth
Abstract: Beginning in the 1930s, neighborhood racial composition was an explicit determining factor in the evaluation of U.S. home values. This deliberate practice was outlawed in the 1960s and 1970s, but the correlation between neighborhood racial composition and home values persists. Using Census Bureau data from 1980 to 2015, the present study investigates the changing relationship between neighborhood racial composition and home appraisals, as well as the mechanisms that drive it. Contrary to what is often presumed, neighborhood racial composition was a stronger determinant of appraised values in 2015 than it was in 1980. Results suggest this is primarily due to contemporary appraising practices. Specifically, the use of the sales comparison approach has allowed historical racialized appraisals to influence contemporary values and appraisers' racialized assumptions about neighborhoods to drive appraisal methods. These findings provide strong evidence that persistent racial inequality is driven in part by perpetual devaluing of communities of color and they suggest further regulation is required to foster equity.